High‐resolution facies analysis of a coastal sabkha in the eastern Gulf of Salwa (Qatar): A spatio‐temporal reconstruction. Issue 3 (12th October 2021) - Engel, Max; Strohmenger, Christian J.; Peis, Kim T.; Pint, Anna; Brill, Dominik; Brückner, Helmut
Abstract: Sabkhas are key landforms along the southern coast of the Arabian Gulf and represent modern analogues for depositional and diagenetic processes controlling properties and quality of ancient hydrocarbon‐bearing carbonates. While previous investigations of coastal sabkhas in Qatar have mainly focused on dolomitization processes, presented here is one of the first studies reconstructing facies changes and coastal formation in great detail. In the sabkha of Al‐Kharayej (Gulf of Salwa), fifteen different facies types were distinguished based on twelve sediment cores, two trenches, as well as grain‐size distribution, X‐ray powder diffraction, thin section and microfossil analyses. Age estimates were based on seventy‐eight 14 C‐AMS and optically stimulated luminescence data. The sabkha parasequence comprises pre‐transgressive dune sands, a thin, transgressive layer of reworked dune material, a mid‐energy open‐coast to open‐lagoon facies, a low‐energy lagoon facies, saline lake facies (salina: swallow‐tail gypsum and gypsum mush) and the supratidal sabkha characterized by diagenetic overprinting (buckled gypsum crusts and halite crust). Transgressive marine flooding created open‐coast to open‐lagoon sedimentation after ca 7000 cal yr bp, followed by initial spit formation at the northern sabkha end at the beginning of the relative sea‐level highstand (6000 cal yr bp ). This main outer spit prograded southward and a more narrow, low‐energy spit, diverted landward, closing a small lagoon in the northern sabkha 4500 to 4000 cal yr bp . The falling relative sea‐level and longshore drift intensified the southward extension and widening of the main spit, and the main lagoon became more shallow. At 2000 to 1500 cal yr bp, the outer spit had almost closed the main lagoon, leading to salina and, finally, sabkha conditions. It is shown how specific local conditions (coastline orientation; wind, wave, tidal energy, longshore drift; depositional relief; sediment sources) created a spit‐controlled sabkha that is genetically distinct from the classical model of shore‐perpendicular accumulation of coarser sediment during high tides or storms.